Brand Animosity as a Driver of Digital Boycotts: How Socio-Political Issues Shape Generation Z Consumer Behaviour in Indonesia - Annisa Tusolihah; Andi Azhar (Tecno Scientifica Publishing, 2026)
The rise of digitally mediated consumer activism has fundamentally altered the dynamics between global brands and value-conscious consumers. This study investigates how socio-political issues activate brand animosity among Generation Z consumers in a Muslim-majority emerging market context and how such animosity translates into digital boycott participation. The research adopts a qualitative exploratory design grounded in an integrative framework that combines Brand Animosity Theory, the Theory of Planned Behavior, and Cognitive Dissonance Theory. Data were collected through netnographic observation across TikTok, X (formerly Twitter), and Instagram between December 2024 and January 2026, supplemented by twelve semi-structured, in-depth interviews with purposively selected Generation Z respondents aged 18–24 years. Theoretical saturation was assessed through systematic monitoring of code novelty rates, with the final two interviews yielding fewer than 5% new codes. Reflexive thematic analysis was applied to the interview transcripts and netnographic field notes, with inter-coder agreement testing conducted on a 25% subsample, yielding a Cohen's kappa value of 0.81. The findings reveal three primary mechanisms through which socio-political issues generate brand animosity: moral-religious framing of geopolitical conflict, viral social contagion of negative brand associations, and collective identity reinforcement through digital solidarity rituals. Cognitive dissonance resolution and digital social norm pressure operate as critical mediating pathways between brand animosity and actual boycott participation. The study proposes a tentative construct labelled networked moral outrage, conceptualised as a digital-era extension of brand animosity that complements existing constructs of online moral outrage and digital activism while remaining grounded in brand-level affect. The findings have important implications for brand crisis communication strategies in digitally connected emerging markets.